Impact of polycyclic aromatic hydrocarbons and heteroatomic bridges (N, S, and O) on optoelectronic properties of 1, 3, 5‐triazine derivatives: A computational insight. (20th August 2020) - V.M., Vidya; Chetti, Prabhakar
Abstract: The theoretical investigation of four series of 1, 3, 5‐triazine derivatives (viz., TN, NTN, STN, and OTN series), which are substituted with polycyclic aromatic hydrocarbons, is carried out by employing density functional theory and time dependent‐density functional theory. The triazine ring acts as electron acceptor (A ) and polycyclic aromatic hydrocarbons act as electron donors (D ). The aromatic hydrocarbons like benzene, naphthalene (two fused rings), anthracene (three fused rings), and pyrene (four fused rings) are substituted on 1, 3, 5‐triazine core by means of a bridging heteroatom N, S, and O in the case of NTN, STN, and OTN series of molecules, respectively, whereas polycyclic aromatic hydrocarbons are directly connected to 1, 3, 5‐triazine in the case of TN series of molecules. The present work aims at examining the impact of number of fused aromatic rings and changing the bridging unit between electron acceptor and electron donor on absorption properties, HOMO‐LUMO gap and first hyperpolarizabilities of molecules under study and provides important insights for architecture of organic molecules for applications in organic optoelectronics. Abstract : The current work reports the variation of absorption properties and first hyperpolarizabilities of PAHs connected to 1, 3, 5‐triazine core with an increasing number of fused aromatic rings and with change in bridging atom between donor (D ) and acceptor (A ). The successive increase in the number of fused aromatic rings (benzene, naphthalene and anthracene) from XTN1, XTN2 and XTN3 (X = no bridge/N/S/O) causes successive reduction of transition energy ( E ge ), induces significant redshift in absorption and enhances the first hyperpolarizability.